Michel de Montaigne. Per una lettura degli Essais (ENTHYMEMA, 2012)
In this article we reflect on the style the thought of Montaigne’s Essais. In particular we underline the ability of the thinker to attach a new meaning to traditional terms, recovered in unprecedented acceptations. For example, we can find a notion of form that can include multiplicity without force it into the “One”. Montaigne refuses the traditional conception of the form as a rigid essence, as a whole of traits and properties; the “identity of the human subject” – the “humaine condition” – is rather a flexible condition, i.e. open to divergent fates. Montaigne’s thought can therefore be interpreted as a thought of flexibility.